2019
DOI: 10.1088/1755-1315/388/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting date and spraying of humic acid in the growth traits and active compounds of Fenugreek (Trigonella foenum – graecum L)

Abstract: The study was conducted at the Crops Research Station, College of Agriculture, University of Diyala during the years 2017-2018 to evaluate the effect of planting dates and spraying of humic acid in the growth characteristics and active compounds of Fenugreek (Trigonella foenum –graecum L). The experiment was carried out according to factorial arrangement in a complete randomized blocks design (RCBD) with three replicates and two factors, the first include planting dates (15/10,1/11,15/11) and the second is spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…It is noticed from the data of the previous tables (1, 2, 3, 4, 5) that the second date exceeded in the attribute (plant height, leaf area, number of pods) it may be because the plants were planted at an appropriate time from the other two dates and thus the plant benefited from the appropriate environmental conditions During its first stages of growth coincided with the ideal temperatures, humidity and intensity of lighting that stimulated vegetative growth as well as the growth of lateral buds, which leads to an increase in the rate of photosynthesis [7] and thus obtaining a good plant. Planting plants at the ideal time for growth leads to an increase in the leaf area of the plant and an increase in the process of photosynthesis, which leads to the transmission of its results to the pod, and the number of pods increases.…”
Section: Discussionmentioning
confidence: 99%
“…It is noticed from the data of the previous tables (1, 2, 3, 4, 5) that the second date exceeded in the attribute (plant height, leaf area, number of pods) it may be because the plants were planted at an appropriate time from the other two dates and thus the plant benefited from the appropriate environmental conditions During its first stages of growth coincided with the ideal temperatures, humidity and intensity of lighting that stimulated vegetative growth as well as the growth of lateral buds, which leads to an increase in the rate of photosynthesis [7] and thus obtaining a good plant. Planting plants at the ideal time for growth leads to an increase in the leaf area of the plant and an increase in the process of photosynthesis, which leads to the transmission of its results to the pod, and the number of pods increases.…”
Section: Discussionmentioning
confidence: 99%
“…Plant height values obtained as a result of this study Sade et al (1994) were found to be similar to the results reported. Majid et al (2019) reported that plant height could change between 46.00-84.89 cm in their study in which they examined the effect of planting date and humic acid spraying on the growth characteristics of fenugreek (Trigonella foenum-graecum L.). They obtained different results from the results we obtained with this study.…”
Section: Plant Heightmentioning
confidence: 99%
“…The number of seeds per pod at both planting times was higher than the values reported by Yılmaz and Akdağ (1994) (5.4-7.8 units). Majid et al (2019) examined the effect of planting date and humic acid spraying on the growth characteristics of fenugreek (Trigonella foenum-graecum L.) and found the number of seeds to be 14.44 seed plant -1 . The results we obtained with this study Majid et al (2019) was found to be similar.…”
Section: Number Of Seeds Per Podmentioning
confidence: 99%
“…2.1.1. The Percentage of Protein in the Seeds % It was estimated using the Caldall device after knowing the nitrogen concentration in the seeds, then calculating the protein percentage by multiplying the nitrogen concentration by a constant factor of (6.25) according to the method of Daly and Al-Hakim (1987) [11].…”
Section: Studied Traitsmentioning
confidence: 99%